An energy-efficient decentralised communication protocol for a network of uniformly distributed sensors polled by a wireless transceiver - Verdone, R. (2004 IEEE Itnernational Conference on Communications, 2004)
In this paper a network of sensors uniformly and randomly distributed over a plane large enough to be considered infinite is considered. The author formalises a particular problem, where a supervisor wants to collect the sensor data from a specific region around him/her. This region is assumed to be small, so that no routing aspects have to be considered, as direct communication between sensor nodes and supervisor can take place. The losses characterising the communication links between them follow a power law affected by a random component. The system constraints are related to an application-driven maximum value of latency and the requirement of a minimum life duration of sensors. Propagation, physical and multiple access problems are jointly addressed through a complete analytical description. The evaluation of the statistics of the number of packets successfully received by the supervisor is carried out through the use of the results of a statistical study, taken from the literature, on the connectivity of nodes uniformly and randomly distributed over the infinite plane and subject to log-normal distributed loss. These results have been suitably applied to the sensor network, which requires the investigation of aspects related to the packet capture effect, the probability distribution of audible sensors, etc.